2017
DOI: 10.3390/molecules22071172
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Novel Coumarin Derivatives, Antimicrobial Analysis, Enzyme Assay, Docking Study, ADMET Prediction and Toxicity Study

Abstract: The work reports the synthesis under solvent-free condition using the ionic liquid [Et3NH][HSO4] as a catalyst of fifteen novel 3-((dicyclohexylamino)(substituted phenyl/heteryl)-methyl)-4-hydroxy-2H-chromen-2-onederivatives 4a–o as potential antimicrobial agents. The structures of the synthesized compounds were confirmed by IR, 1H-NMR, 13C-NMR, mass spectral studies and elemental analyses. All the synthesized compounds were evaluated for their in vitro antifungal and antibacterial activity. The compound 4k be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 32 publications
3
42
1
Order By: Relevance
“…In the continuation of our previous work [11][12][13][14][15][16][17][18][19][20][21][22][23] , it was confirmed that until now none of the methods had used such a mild and green catalyst and solvents for Dakin oxidation. The designed method is suitable for the conversion of substituted benzaldehydes to its consequent substituted phenols.…”
Section: Introductionmentioning
confidence: 72%
“…In the continuation of our previous work [11][12][13][14][15][16][17][18][19][20][21][22][23] , it was confirmed that until now none of the methods had used such a mild and green catalyst and solvents for Dakin oxidation. The designed method is suitable for the conversion of substituted benzaldehydes to its consequent substituted phenols.…”
Section: Introductionmentioning
confidence: 72%
“…[a] Molecular weight of the molecule, [b] Predicted octanol/water partition co‐efficient log P (acceptable range: −2.0 to 6.5) ,. [c] Predicted aqueous solubility; S in mol/L (acceptable range: −6.5 to 0.5).…”
Section: Resultsmentioning
confidence: 99%
“…All the novel compounds from both series, the carboxamides 3a – m and Schiff base carbohydrazides 5a – l , were screened for in vitro antibacterial activity against Pseudomonas aeruginosa, Escherichia coli , Klebsiella pneumoniae , Salmonella typhi and Bacillus subtilis . Methods, as recommended by the National Committee for Clinical Laboratory Standards (NCCLS), were used to determine the corresponding minimum inhibitory concentration (MIC) values [ 27 , 28 , 29 , 30 ]. Stock solutions were prepared in dimethyl sulfoxide (DMSO) and DMSO alone served as solvent control.…”
Section: Resultsmentioning
confidence: 99%